Sector Classification and Economic Inequality in Cilacap Regency - Fahrizal (INQUISITIVE : International Journal of Economic, 2024)
The economic growth of Cilcap Regency as seen from the total GDP in the 2015-2022 period shows fluctuations, so an analysis is needed that aims to find out the 17 sectors that contribute the most in the formation of total GDP and equitable distribution of regional development to reduce regional economic inequality. Therefore, this study aims to classify 17 sectors into 4 clusters, namely superior, potential, developing and underdeveloped and income inequality in Cilacap Regency. The research method used 2 analyses, namely, Location Quotient (LQ) analysis and Williamson Index (IW) analysis. The data source comes from the Central Statistics Agency of Cilacap Regency and Central Java Province, vulnerable in the 2015-2022 period. The results of the study show that the sector classification is the leading category: development and excavation, potential: processing industry, developing: 15 other sectors and lagging: no sectors are categorized as underdeveloped. The level of economic inequality in the Cilacap Regency area in 2015-2022 has decreased from 0.31 to 0.17, this indicates that the economic development of Cilacap Regency is getting closer to evenness, this is because the IW value < 0 which is close to the value of 0. Although there is still a regional economic deficit, it is still categorized as low because the IW value < 0.3.